Gene Therapy for the Inner Ear: Challenges and Promises - Ryan, Allen F. (Adv Otorhinolaryngol, 2009)
Since the recognition of genes as the discrete units of heritability, and of DNA as their molecular substrate, the utilization of genes for therapeutic purposes has been recognized as a potential means of correcting genetic disorders. The tools of molecular biology, which allow the manipulation of DNA sequence, provided the means to put this concept into practice. However, progress in the implementation of these ideas has been slow. Here we review the history of the idea of gene therapy and the complexity of genetic disorders. We also discuss the requirements for sequence-based therapy to be accomplished for different types of inherited diseases, as well as the methods available for gene manipulation. The challenges that have limited the applications of gene therapy are reviewed, as are ethical concerns. Finally, we discuss the promise of gene therapy to address inherited and acquired disorders of the inner ear.